Factors associated with knowledge about family planning and access to sexual and reproductive health services by sexually active immigrant youths in Hillbrow, South Africa: a cross-sectional study - Nkechi Obisie-Nmehielle; Ishmael Kalule-Sabiti; Martin Palamuleni (BMC, 2022)
Plain language summary Access to SRH services by adolescents and youths has been a serious public health concern globally. In South Africa, universal access to health care including reproductive health care services is contained in Sect. 27 of the Constitution. The country is committed to the 2030 Agenda of the SDGs with the theme "leaving no one behind". The objective of this study was to examine the factors associated with knowledge about family planning and access to SRH services among sexually active immigrant youths in Hillbrow, South Africa. Interviewer-administered questionnaires were used to collect information on the socio-demographic, migration, and reproductive health characteristics from 439 sexually active immigrant youths in Hillbrow during December 2019. The data were analysed to assess the factors associated with knowledge about family planning and access to SRH services. The findings show that 46% of the immigrant youth had poor knowledge about family planning, while 35% had no access to SRH services, 42% had some access and only 23% had access. The study showed that the factors associated with knowledge about family planning are female respondents, from the rich income group, those in the older age category, those who received information about family planning 6-months prior to the survey and those using a contraceptive at the time of the survey. The factors associated with having no access to SRH services were those respondents having completed secondary education and higher, from the rich income group, undocumented immigrants, those respondents having experienced discrimination in Hillbrow, youths not having received information about family planning prior to the survey, and those not using a contraceptive. It is important to make access to SRH services available to immigrant youths to prevent associated negative SRH outcomes among the youths.